KAJIAN PEMBERSIHAN DAN PENDINGINAN GAS PRODUKSI GASIFIKASI BIOMASSA MENGGUNAKAN FILTER SERABUT KELAPA - , AKBAR RAKHMATULOH; , Dr. Ir. Bambang Purwantana, M.Agr. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The main products are expected from the biomass gasification is a synthetic gas (syngas) which includes CO, H2, and CH4. Nevertheless, in the gasification process also resulted with byproducts such as tar, steam, and ash which can reduce the quality of the gas. Tar and ash separation from syngas components as well as the cooling of gas is needed to improve the quality of gas. A relatively inexpensive way to achieve this goal is to use biomass fiber for gas filter. This experiment was conducted to analyze the performance of the syngas cleaning and cooling by using coconut fiber as a gas filter on the downdraft. The experiment was conducted by varying coconut fiber densities, respectively 24,88 kg/m3, 34,83 kg/m3 and 44.79 kg/m3, on the gas filter. The foam material (spons) is used as a comparison to the coconut fiber. The measured variable is the amount of tar that can be separated, the temperature reduction that can be reached from each treatment as well as the effective time of gas production. To determine the effect of treatment on gasification parameters, the statistical analysis with Completely Randomize Design method (CRD) using Analysis of Variance (ANAVA) was used. The experiment result showed that coconut fiber densities does not significantly affect on the temperature reduction, tar filtering and gasifier stove flame intensity. The use of coconut fiber density of 34,83 kg/m3 on the cleaning and cooling of the gasification gas production using coconut fiber filter provides the best performance with an average temperature reduction of 4,28 oC, the average filtering tar 280 grams and the gasifier stove average time of flame 27,33 minutes.